Pemetaan Wilayah Dakwah: Pengembangan Dakwah Berorientasi Perubahan - Aep Kusnawan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
Mapping means the preparation of drawings and instructions. If the mapping is associated with the propagation region then it means the preparation of drawings and instructions on the various potentials in the territory of the propaganda. Among the mission objective is to improve the condition of a society. Therefore preachers should initiate activities to determine the condition of objects mission objective, which is then followed by various missionary activities proper, effective and efficient. Therefore, propaganda mapping effort is a very basic need. Maps can be useful for analyzing object simplify propaganda, so that preachers can properly present the materials, methods and media used in propaganda, in accordance with the conditions and needs of the local community. Besides the diversity of objective conditions missionary territory, demanding the diversity of the various models of propaganda, and the need for diversity in the measurement of the level of development of each region where the mission. So from time to time, the activities carried out and the results are obvious progression.